Smart final year project archive system using laravel framework with email notification (SFYPAS) / Abidah Mat Taib - Mat Taib, Abidah; Mohd Shukri, Noor Atirah; Ahmad Zukri, Nurul Hidayah; Ghazali, Norlizawati (UiTM Cawangan Perlis, 2020)
Final Year Project (FYP) is a compulsory requirement for graduation of every bachelor programme in Universiti Teknologi MARA (UiTM). Finding a topic for the final year project is quite challenging. However, being able to access previous FYP thesis helps students to generate some ideas. Supervisors and lecturers can also determine whether the proposed project is already among the previous research project or a new one. Unfortunately, the past FYP thesis is usually kept in a specific thesis room. Hence, this will make going to the thesis room and searching the thesis for references quite burdensome. The lack of electronic management for FYP thesis causes several problems in arrangement and search methods. This project aims to develop Smart Final Year Project Archive System (SFYPAS) using Laravel Framework and evaluate the system in terms of Technology Acceptance Model (TAM). SFYPAS is developed using Laravel framework and the methodology used throughout the project is using Software Development Life Cycle (SDLC). The system was tested based on its functionality, user acceptance with TAM and heuristic evaluation by an expert. It was tested on thirty respondents who shared their feedback by answering a set of questionnaires upon completing the testing. The result shows that the mean for user acceptance with TAM in terms of perceived ease of use is 4.27, while perceived usefulness is 4.47. Thus, it shows that the respondents are satisfied with the system in terms of its perceived usefulness. In conclusion, this research has achieved the objectives where it eases the user by providing a web-based smart archive system as a platform to access the past FYP thesis. For future work, the system can be improved by adding a search engine that implements any searching algorithm to yield better results.